(untitled) (Journal of Parents and Teachers, 2026)
Iñaki is a preschooler, about to start primary school. It seems that something is preventing him from getting to grips with reading and writing. His mother is worried, and this leads her to consider the problem – and almost diagnose it – as if the boy were refusing to read in defiance of her. It is possible that, rather than a problem with reading and writing, this is a mother-son communication issue. The boy is looking for a way to express something that is causing him distress, but he doesn’t know how to do so. ‘Not wanting to’ is merely a symptom of his unease at not having the relationship with his mother that he would like. It will be important for the mother to approach the problem from a different perspective, one that allows her to find the right words so that the boy can experience the satisfaction of communicating with her without having to resort to his ‘rebellion’.